Effects of the drug combination memantine and melatonin on impaired memory and brain neuronal deficits in an amyloid‐predominant mouse model of Alzheimer's disease. (18th September 2019) - Jürgenson, Monika; Zharkovskaja, Tamara; Noortoots, Aveli; Morozova, Margarita; Beniashvili, Allan; Zapolski, Max; Zharkovsky, Alexander
Abstract: Objectives: Alzheimer's disease (AD) is a neurodegenerative disorder with no cure. Limited treatment options available today do not offer solutions to slow or stop any of the suspected causes. The current medications used for the symptomatic treatment of AD include memantine and acetylcholine esterase inhibitors. Some studies suggest that melatonin could also be used in AD patients due to its sleep‐improving properties. Methods: In this study, we evaluated whether a combination of memantine with melatonin, administered for 32 days in drinking water, was more effective than either drug alone with respect to Aβ aggregates, neuroinflammation and cognition in the double transgenic APP/PS1 (5xFAD) mouse model of AD. Key findings: In this study, chronic administration of memantine with melatonin improved episodic memory in the object recognition test and reduced the number of amyloid aggregates and reactive microgliosis in the brains of 5xFAD mice. Although administration of memantine or melatonin alone also reduced the number of amyloid aggregates and inflammation in brain, this study shows a clear benefit of the drug combination, which had a significantly stronger effect in this amyloid‐dominant mouse model of AD. Conclusion: Our data suggest considerable potential for the use of memantine with melatonin in patients with AD.